2015
DOI: 10.1051/epjconf/20159301039
|View full text |Cite
|
Sign up to set email alerts
|

Observation of low-lying resonances in the quasicontinuum of195,196Pt and enhanced astrophysical reaction rates

Abstract: Abstract. An excess of strength on the low-energy tail of the giant dipole resonance recently has been observed in the γ-decay from the quasicontinuum of 195,196 Pt. The nature of this phenomenon is not yet fully investigated. If this feature is present also in the γ-ray strength of the neutron-rich isotopes, it can affect the neutron-capture reactions involved in the formation of heavy-elements in stellar nucleosynthesis. The experimental level density and γ-ray strength function of 195,196 Pt are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Results on 112 Cd [7] and 116 Sn [8,9] suggest that additional strength could be expected for 115 In at energies between 6 and 10 MeV. In these studies, nuclear level densities and PSFs below the neutron separation energy are extracted from ( 3 He ,αγ ) and ( 3 He , 3 He γ ) reaction data using the Oslo method [11]. Additional dipole strength is introduced on top of the GLO E1 PSF to reproduce the data, in the form of a Gaussian contribution.…”
Section: B Low-energy Enhancement In the Photon Strengthmentioning
confidence: 93%
See 2 more Smart Citations
“…Results on 112 Cd [7] and 116 Sn [8,9] suggest that additional strength could be expected for 115 In at energies between 6 and 10 MeV. In these studies, nuclear level densities and PSFs below the neutron separation energy are extracted from ( 3 He ,αγ ) and ( 3 He , 3 He γ ) reaction data using the Oslo method [11]. Additional dipole strength is introduced on top of the GLO E1 PSF to reproduce the data, in the form of a Gaussian contribution.…”
Section: B Low-energy Enhancement In the Photon Strengthmentioning
confidence: 93%
“…In the context of astrophysical neutron capture rate evaluations, it has been shown that the low-energy part of the PSF can greatly impact stellar rates [1][2][3][4]. Much attention has thus recently been paid to the understanding of additional low-energy resonances in the PSF, observed sitting around the neutron emission threshold energy on the low-energy tail of the giant dipole resonance (GDR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation